“They Always Make It Right. We Can Do That for Everybody”: Young Adolescents Considering (In)Justice When Reading - Caleb Chandler; Kaitlin Wegrzyn (Middle Grades Review, 2022)
This paper draws on Bakhtin’s (1981) notions of discourse and ideological becoming to investigate how adolescents’ experiences with young adult literature and other texts might inform their thinking around issues of social justice. We engaged in a number of activities with the young adolescent participants: thought maps, illustrations of poignant scenes, written accounts of personal experiences, and focus group interviews. Using these activities as our data for this paper, we explain how the young adolescent participants called upon discourses of social justice to engage in the process of ideological becoming. Thus, the paper concludes that texts have the potential to affect students’ ways of thinking and being in profound ways.
Keywords: young adolescents; literacy; ideological becoming